Mechanisms of cartilage damage in gout and hyperuricemia - E. V. Panina (Научно-практическая ревматология, 2024)
The prevalence of hyperuricemia (HU), which can be considered the first stage of gout formation, varies in different countries and tends to increase. Uric acid (UA), even in its dissolved form, activates damage and potentiates the death of articular cartilage cells through direct cytotoxicity and a number of other pathogenetic mechanisms. The possible association of HU and osteoarthritis may be due to a number of common pathogenetic mechanisms, but the direction of this relationship is still a debatable issue. The accumulated data suggest the need for a deeper study of the relationship between gout and HU with pathological processes leading to the development and progression of osteoarthritis and bone metabolism disorders.